The Impact Assessment of Forest Degradation on Peoples Livelihood: The Case of Harena Buluq Woreda Bale Eco Region, Southeast Ethiopia: Impact Assessment of Forest Degradation - Takele, Elsabet (The Indonesian Forestry Certification Cooperation, 2024)
In developing countries like Ethiopia, forest degradation, characterized by the decline in forest cover and diminished capacity to provide essential goods and services, presents significant environmental, social, and economic challenges. The purpose of this study is to assess the effects of forest degradation on the way of life for the people living in the southeast Ethiopian woreda of Harena Buluq. Examining how forest degradation affects local livelihoods with a particular emphasis on livelihood strategies and the degree of reliance on forest resources is the main goal. In order to obtain qualitative insights, data was gathered by means of a combination of secondary sources and key informant interviews, which were complemented by on-site observations of the consequences of forest degradation. After gathering, the data was examined and shown. The findings underscore the multifaceted impact of forest degradation on the socio-economic fabric of communities in Harena Buluq, highlighting the urgent need for targeted interventions to mitigate its adverse effects and promote sustainable livelihood practices.